1-Allyl-4-(1,3-benzothiazol-2-yl)-5-methyl-2-phenyl-1H-pyrazol-3(2H)-one - Chakib, I.; Zerzouf, A.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, C20H17N3OS, is a 1H-pyrazol-3(2H)-one having aromatic 4-(1,3-benzothiazol-2-yl)-and 2-phenyl substituents. The five-membered ring and fused ring system are planar, the r.m.s. deviations being 0.021 and 0.005 angstrom, respectively. The five-membered ring is aligned at 7.9 (2)degrees with respect to the fused-ring system. The allyl and phenyl parts of the molecule are both disordered over two positions in a 1: 1 ratio. Weak intermolecular C-H center dot center dot center dot O hydrogen bonding is present in the crystal structure.